RESEÑA de : Niranjana, Tejaswini. Sitting Translation : History, Post-structuralism, and the Colonial Content.Berkeley; Los Ángeles; California : University of California Press, 1991 - Álvarez, María Antonia (Epos : Revista de filología, 1996)
-